The Role of Self Efficacy on Academic Procrastination among University Student - Purnomo, Reza Asep Adi; Susanto, Aiko Rahmalilla Ananda; Oktavianisa, Nur Afni (Jurnal Psikologi Teori dan Terapan, 2024)
Abstract Background: Not a few students deliberately postponed their assignments. Academic procrastination often occurs in students because of the high workload. Self-efficacy is believed to influence procrastination. Objective: This research aims to determine the extent to which students' self-efficacy plays a role in their level of academic procrastination in carrying out lecture assignments. Method: Research uses descriptive quantitative methods with non-experimental research types, and result analysis using simple regression analysis. The subject used is a student of Psychology at the State University of Surabaya. Results: The results of this study showed that self-efficacy and procrastination have a negative relationship, which means that if self-efficacy is improved then procrastination in students is decreased and vice versa. Self-efficacy variables give an effective contribution of 23.2% to the procrastination variable which means self-efficacy is not the most crucial thing in affecting procrastination because there are still 76.8% other factors. Conclusion: To reduce procrastination, self-efficacy is required because the higher the self-efficacy of a person, the lower the tendency to procrastination.   Abstrak Latar belakang: Tidak sedikit mahasiswa sengaja menunda tugas mereka. Prokrastinasi akademik sering terjadi pada mahasiswa karena beban kerja yang tinggi. Efikasi diri dipercaya mempengaruhi prokrastinasi. Tujuan: Penelitian ini bertujuan untuk menentukan sejauh mana efikasi diri mahasiswa memainkan peran dalam tingkat prokrastinasi akademik mereka dalam melakukan tugas kuliah. Metode: Penelitian menggunakan metode kuantitatif deskriptif dengan jenis penelitian non-eksperimental dan analisis hasil menggunakan analisis regresi sederhana. Subjek yang digunakan adalah mahasiswa Psikologi Universitas Negeri Surabaya. Hasil: Hasil penelitian ini menunjukkan bahwa efikasi diri dan prokrastinasi memiliki hubungan negatif, yang berarti bahwa jika efikasi diri ditingkatkan maka prokrastinasi pada mahasiswa berkurang dan begitupula sebaliknya. Variabel efikasi diri sendiri memberikan kontribusi efektif sebesar 23,2% untuk variabel prokrastinasi yang berarti efikasi diri sendiri bukanlah hal yang paling penting dalam mempengaruhi prokrastinasi karena masih ada 76,8% faktor lain. Kesimpulan: Untuk mengurangi prokrastinasi, efikasi diri diperlukan karena semakin tinggi efikasi diri seseorang, semakin rendah kecenderungan untuk prokrastinasi.